Guest Editor’s Introduction: The Essential Tension of Creativity and Rationale in Software Design - Carroll, John (Human Technology, 2010)
Creativity and rationale connote two faces of design that are sometimes viewed as complementary: envisioning new worlds through intuitive strokes of innovation versus analyzing reasons and tradeoffs to guide the development of new artifacts and systems. Because it is frequently the case that different practitioners and researchers, and different design disciplines, prize one or the other more highly, there is not only a contrast, but also a lack of integration between creativity and rationale.